English Language Competence and Motivation of Grade 12 Students in Relation to Academic Performance: Implications for Educational Intervention - Perez, Juna Mae O.; Vibal, Jobell Cris T. (Future Science / FSH-PH Publications, 2025)
This study determined the English language competence and learning motivation of Grade 12 students and their relationship to academic performance. Using standardized questionnaires, data were collected from 201 students. The findings revealed that students are moderately competent in English and highly motivated to learn. However, neither language competence nor motivation showed a significant relationship with academic performance.